Effects of interval training on hemodynamic variables after coronary artery bypass graft: a meta-analysis - Zehra, Fatima; Aslam, Sehrish; Saeed, Mehjabeen (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the combined impact of interval training programme on haemodynamic variables, specifically blood pressure and heart rate, in patients having undergone coronary artery bypass graft surgery. Methods: The meta-analysis was conducted from October to December 2022, and comprised search on PubMed, MEDLINE, Web of Science, PeDro, EMBASE, Science Direct, Cochrane Central Register of Controlled Clinical Trials, Google Scholar and Scopus electronic databases by two researchers independently for literature published between 2009 and 2020 related to the effects of interval training on coronary artery bypass graft patients. Meta-analysis was then performed to analyse the effects of an interval training on systolic blood pressure, diastolic blood pressure, and heart rate. The meta-analysis was performed in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Results: Of the 122 studies initially located, 7 were related to the effects of different forms of interval trainings and their impact on systolic and diastolic blood pressure of the patients, and 5 studies analysing the effects of interval trainings on heart rate. Interval training showed mild improvement in decreasing SBP compared to control groups. Standardized mean difference suggested an effect size of -0.226 in random effect model (I2=52.01; p=0.064). Similarly, a small effect size of 0.136 (I2=39.19%, p=0.14) was observed for diastolic blood pressure. Also, there was a small effect size of 0.155 (I2= 28.08, p=0.23) observed for heart rate. ---Continue